A Markov chain analysis of emotional exchange in voice-to-voice communication: testing for the mimicry hypothesis of emotional contagion - Lopes, M.; Navarro, J.; Caetano, A.; Junça Silva, A. (Human Communication Research, 2015)
Mimicry is a central plank of the emotional contagion theory; however, it was only tested with facial and postural emotional stimuli. This study explores the existence of mimicry in voice-to-voice communication by analyzing 8,747 sequences of emotional displays between customers and employees in a call-center context. We listened live to 967 telephone interactions, registered the sequences of emotional displays, and analyzed them with a Markov chain. We also explored other propositions of emotional contagion theory that were yet to be tested in vocal contexts. Results supported that mimicry is significantly present at all levels. Our findings fill an important gap in the emotional contagion theory; have practical implications regarding voice-to-voice interactions; and open doors for future vocal mimicry research.